PENGEMBANGAN VIDEO PEMBELAJARANUNTUK PESERTA DIDIK KELAS X IPA MAN 1 PASAMAN BARAT - Abdul Razak; Wirda Taufik; Dwi Hilda Putri; Irdawati Irdawati (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to produce learning videos for Bacteria and Protists using Sparkol Videoscribe software for class X IPA students that are valid, practical, and effective. This research method is research and development (research and development) using the Plomp development model. This development stage consists of three stages, namely the preliminary research phase, the development or prototyping phase, and the assessment phase. The results of this study indicate that the developed learning videos have a validity value of 85.63% with a very valid category based on expert judgment. The practicality assessment by the teacher was 89.13% in the very practical category and the large group evaluation assessment by students obtained a practicality value of 87.69% in the very practical category. The results of the effectiveness test showed that the class that used learning videos had higher average competency values of knowledge, attitudes, and skills, compared to classes that did not use learning videos. It can be concluded that the learning videos that have been developed are in the category of very valid, very practical, and very effective for increasing students' learning competence